1958
DOI: 10.1002/srin.195802678
|View full text |Cite
|
Sign up to set email alerts
|

Die Temperaturabhängigkeit der Verzunderung von reinem Eisen in Sauerstoff

Abstract: Neumessung der Konstanten bei der Verzunderung von Elektrolyteisen von 480 bis 1080° C in Sauerstoff bei Atmosphärendruck unter Verwendung eines Fallbügelreglers zur Vermeidung von Übertemperaturen. Vergleich der Ergebnisse mit Angaben aus dem Schrifttum. Bedeutung der Temperaturen von 566, 579, 616, 755 und 910° C für die Verzunderung von Eisen. Mikroskopische Untersuchungen der Zunderschichten, besonders der Magnetitausscheidungen im Wüstit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2
2

Year Published

1959
1959
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 0 publications
2
8
2
2
Order By: Relevance
“…It was thought that this was because the chemical potential of oxygen was insufficient for magnetite formation. The parabolic rate constants obtained were only 10 to 20 pct smaller than those obtained by Davies et al [27] and Schmahl et al [28] for iron oxidation in oxygen. The reduced oxidation rates were thought to be the result of absence of magnetite.…”
Section: Possible Mechanisms Responsible For the Parabolic Growthcontrasting
confidence: 58%
“…It was thought that this was because the chemical potential of oxygen was insufficient for magnetite formation. The parabolic rate constants obtained were only 10 to 20 pct smaller than those obtained by Davies et al [27] and Schmahl et al [28] for iron oxidation in oxygen. The reduced oxidation rates were thought to be the result of absence of magnetite.…”
Section: Possible Mechanisms Responsible For the Parabolic Growthcontrasting
confidence: 58%
“…On the contrary, Hussey et al < 5 J<sJ reported that unusual kinetic behavior was observed up to 50 h in the oxygen pressure from 10-o. 9 to 10 4 • 1 Pa between 723 and 823 K due to the separation of oxide film from the metal surface under the reduced pressure.…”
Section: Introductionmentioning
confidence: 99%
“…These alloys exist at 1000 "C as austenite up to 1 . The silicon concentration at the alloy internal oxidation zone front in specimens exposed for various times to a 50 vol.…”
Section: Resultsmentioning
confidence: 99%
“…Nodules composed of iron oxides are formed in the silica film on Fe-Si alloys in atmospheres of low oxygen pressures at high temperatures (1,2 ) . These nodules develop into a superficial scale consisting of inner and outer layers of a wustite-fayalite conglomerate and wustite, respectively, in the case of alloys containing up to 2 wt.O/o silicon upon their exposure to atmospheres containing carbon dioxide (3-7).…”
Section: Introductionmentioning
confidence: 99%